(untitled) (Bangladesh Journal of Agricultural Research, 2007)
An experiment was conducted for two consecutive years in the farmers’ field of Palima, Tangail to evaluate the effect of time and depth of placement of urea super granule (USG) on the yield and yield attributes of cabbage during 2003-04 and 2004-05, respectively. USG @ 330 kg per hectare was applied at 0, 10, 15, and 20 days after planting each at 4, 8, and 12 cm depth. The result showed that application of USG at 10 days after transplanting at a depth of 8 cm gave the highest yield of 74.92 and 117.60 t/ha in 2003-04 and 2004-05, respectively. The yield variation was observed due to change of variety (i. e., Atlas 70 in 2003-04 and Autumn Queen in 2004-05). Placement of USG either at 4 cm or 12 cm depth slightly reduced yield than obtained with point placement at 8 cm. USG application later than 10 days of transplanting decreased cabbage yield in both the varieties. Bangladesh J. Agril. Res. 32(2) 2007: 301-306.